Tailored mobile phone text messages as an adjunct to obesity treatment for adolescents. - Woolford, Susan J; Clark, Sarah J; Strecher, Victor J; Resnicow, Kenneth (Journal of Telemedicine & Telecare, 2010)
We examined the use of tailored messages sent to the mobile phones of obese adolescents enrolled in a weight-management programme, as a means of increasing adherence. The feasibility study was conducted in three phases: (1) a library of 90 messages was developed about five weight-related behaviours; (2) a computer application was developed to tailor these messages to participants' characteristics; the SMS messages (text and images) were sent to mobile phones daily; (3) a three-month trial of the intervention was performed with 20 adolescents. Semi-structured interviews were conducted to assess the participants' perceptions of the intervention and the participants', providers' and computer consultants' reports about technology performance. These interviews revealed that participants were enthusiastic about the intervention and most found the messages to be personally relevant. The favourite messages were meal suggestions and recipe ideas. The computer tailoring application performed faultlessly and messages were delivered on schedule and in the desired sequence. Computerized tailored text messaging is a feasible adjunct to multidisciplinary obesity treatment and is acceptable to adolescents as an enjoyable means of improving their adherence to healthy lifestyle practices.